Probiogenomic analysis of Limosilactobacillus fermentum SD7, a probiotic candidate with remarkable aggregation abilities - Thunchanok Yaikhan; Monwadee Wonglapsuwan; Nuntiya Pahumunto; Natakorn Nokchan; Rawee Teanpaisan; Komwit Surachat (Heliyon)
Limosilactobacillus fermentum has gained recognition as a probiotic due to its immunomodulatory properties. In this study, we characterized L. fermentum SD7, which was isolated from the human oral cavity. The genome of L. fermentum SD7 was approximately 2.27 Mb in size, with a 51.1 % GC content. Using comprehensive genome analysis, we compared the genome of L. fermentum SD7 with 153 available genome sequences of L. fermentum strains and categorized the 154 strains into six distinct clades based on core gene single nucleotide polymorphisms. Among the 12,598 orthologous proteins, we identified 910 core genes and 10,169 accessory genes. Our analysis revealed a close similarity between L. fermentum SD7, FS-10, and L13. In addition, L. fermentum SD7 genome contains four strain-specific putative CRISPR-associated genes and lacks antimicrobial resistance and virulence genes. Importantly, we identified 27 genes in L. fermentum SD7 genome that are linked to aggregation ability, which is supported by our probiogenomic analysis. This aggregation ability is considered crucial for the probiotic efficacy of L. fermentum SD7. These findings provide a comprehensive understanding of the genetic composition of L. fermentum and its potential probiotic properties, identifying L. fermentum SD7 as a promising probiotic candidate for use in the food and healthcare industries.